Association of Medicaid expansion with dental emergency department visits overall and by states' Medicaid dental benefits provision - Theodoros V. Giannouchos; Julie Reynolds; Peter Damiano; Brad Wright (BMC, 2023)
Abstract Background Evidence on the association of Medicaid expansion with dental emergency department (ED) utilization is limited, while even less is known on policy-related changes in dental ED visits by Medicaid programs' dental benefits generosity. The objective of this study was to estimate the association of Medicaid expansion with changes in dental ED visits overall and by states' benefits generosity. Methods We used the Healthcare Cost and Utilization Project's Fast Stats Database from 2010 to 2015 for non-elderly adults (19 to 64 years of age) across 23 States, 11 of which expanded Medicaid in January 2014 while 12 did not. Difference-in-differences regression models were used to estimate changes in dental-related ED visits overall and further stratified by states' dental benefit coverage in Medicaid between expansion and non-expansion States. Results After 2014, dental ED visits declined by 10.9 [95% confidence intervals (CI): -18.5 to -3.4] visits per 100,000 population quarterly in states that expanded Medicaid compared to non-expansion states. However, the overall decline was concentrated in Medicaid expansion states with dental benefits. In particular, among expansion states, dental ED visits per 100,000 population declined by 11.4 visits (95% CI: -17.9 to -4.9) quarterly in states with dental benefits in Medicaid compared to states with emergency-only or no dental benefits. Significant differences between non-expansion states by Medicaid's dental benefits generosity were not observed [6.3 visits (95% CI: -22.3 to 34.9)]. Conclusions Our findings suggest the need to strengthen public health insurance programs with more generous dental benefits to curtail costly dental ED visits.